(untitled) (Global Journal of Human-Social Science, 2013)
Linguistic alienation is a wall, which separates the African elite away from their fellow African brothers and sisters. This gap is what we intend to break because it is a kind of cultural alienation, which hinders development in all its ramifications. Our search light in this paper is on cultural and political segregations in Sembène Ousmane’s Xala. We demonstrate that El Hadji Kader Beye, the chief character in the story represents the Senegalese elite in a post-colonial setting while the beggars stand-in for the oppressed masses, who are more than 80% of the country’s population. The oppressed make themselves relevant in the scheme of societal affairs by being the ones that have solution to the xala, a disease of impotence which the protagonist in the story suffers. The spitting act becomes a form of freedom of speech to voice out their mind; especially by showing their displeasure over an exploitative system in the perceived new dispensation. As its purpose, the paper validates the fact that art and society are two interlocking entities. Hanged on sociological criticism, the paper ends with a warning that Africans in general should see the embracement of their culture particularly language as the root of durable and sustainable developments.